Effectiveness of Insulin Injection Technique on Glycemic Control of Fasting Plasma Glucose and HbA1c in Type II DM Patients at Hasanuddin University Hospital: Randomized Controlled Trial - Semi, Herlina; Ahmad, Sitti Musdalifah; Tuti, Meylani; Islam, Alif Muhammad (Faculty of Nursing, Universitas Hasanuddin, 2025)
Aims: To identify the effectiveness of insulin injection techniques (injection method, injectionlocation, insulin pen, and drug dose) on glycemic control of HbA1c and Fasting Plasma Glucose(FPG) in Type II DM patients.Methods: The design of this study was quantitative experimental using a Randomized ControlledTrials (RCT) research design with non-blinding in patients with Type II Diabetes Mellitus whohad received insulin therapy. The sample consisted of 60 Type II DM patients and consisted of30 intervention groups and 30 control groups.Results: There were significant results on the level of knowledge (p=0.043), accuracy of insulinuse (p=0.002), and insulin injection skills (p=0.017) in patients in the intervention group beforeand after education, but there was no significant difference in the control group. In addition, inthe intervention group, there was a substantial and controlled decrease in GDP and HbA1c levelswith a value of (p=0.000), while in the control group, there were no significant results with(p=0.104).Conclusion: Our findings highlight the role of insulin injection techniques (injection method,injection site, insulin pen use, and dosage) in controlling FPG and HbA1c glycemic levels inpatients with Type II DM.